Inclusive Education in Madrasah Ibtidaiyah: A Reflective Study of 21st Century Dynamics, Challenges, and Opportunities - Oktori, Agus Riyan; Yosi Yulizah (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study identifies several problems in the implementation of inclusive education at the Islamic elementary school level in Indonesia, particularly Madrasah Ibtidaiyah (MI). The primary challenges include inadequate facilities and the low-quality quality of educational infrastructure. Then, the lack of competent educators hinders the implementation of effective inclusive education. Many children with physical and mental disabilities have not received equal education. Social issues, including student altercations and the legitimacy of school property, undermine a secure and supportive educational environment. This research employs a qualitative methodology using a literature review approach. Data were obtained from existing literature, including journals, articles, and scientific texts. Data were analyzed using source analysis techniques, ensuring validity through aligning theories from reputable sources to yield relevant and credible research. The conclusion is that inclusive education plays a crucial role in fostering students' talents, potential, and skills, while also imparting essential insights and knowledge applicable to everyday life. This is grounded in the principle that all children possess an equal right to receive a quality education and to develop into mature, intelligent, and ethical individuals. Inclusive education is presently applied in numerous Islamic elementary schools and other formal institutions, emphasizing Islamic values as a framework for learning activities.